Technological Pedagogical and Content Knowledge (TPACK) of Special Education Teachers in Science Instruction for Students with Special Needs - Leni Ambar Cahyani; Nur Azizah; David Evans (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
Integration of technology in science instruction in special education context can be done within the technological, pedagogical, and content knowledge (TPACK) framework. Therefore, special education teachers are expected to have a good level of TPACK. This study aimed to explore the level of teachers TPACK in science instruction for students with special needs and to compare the TPACK level of teachers based on their gender. This research used a quantitative approach with survey method. The respondents of this study were special education teachers (N= 44). The data collection method was through a survey using the TPACK survey instrument. The validation result used the Pearson Correlation showed value per statement ranging from 0.504 - 0.904. Reliability showed in the Cronbach's coefficient Alpha for internal consistency value of 0.856 (high). The data analysis technique used was the descriptive statistical analysis technique and the independent sample t test. The results showed that the total average of all TPACK domain is concluded in good category with mean score 81.29. The t test calculation showed that the t value (0.123) is less than the critical t value in the t table (2.085). The p value obtained was 0.90, greater than 0.05. Therefore, Ho is accepted. The issue of gender equality that has begun to be implemented in Indonesia can be the reason for the loss of technological mastery differences. In conclusion, TPACK mastery of special education teachers in science instruction was not differentiated by teacher gender with p>0.05.